PENGEMBANGAN MODEL PERMAINAN BOTANGGALAH UNTUK PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN SISWA SEKOLAH DASAR - Agus Wiyanto; Tubagus Herlambang; Galih Dwi Pradipta (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Games are awarded to learners should be tailored to the characteristics of the growth rate of learners, this will facilitate the learners in doing akativitas motion. Learning to add to the enrichment of motion in children carried out in the form of the game. Interesting and exciting games for learning in primary schools one of which is the game botanggalah. This research is the development of procedures to cover include; analysis of the product to be developed, develop initial product, expert validation, field trials that include testing small group and large group test, product revision, and the results of product development. Botanggalah game is a game of handball modification using holahop goal. Botanggalah game is a simple game made by learners, the benefits of the game are able to provide botanggalah physical health, increased enrichment of motion, agility and dexterity to train elementary school students. Through his hopes botanggalah game can be one of the solutions to the activities undertaken in relation to the learning process. The desired expectations at least: 1) to increase the interest of students towards learning materials penjasorkes, 2) can be a solution to overcome the boredom of students in learning, which is still relatively monotonous.Â